Morphology of the barren-ground caribou ovary - Dauphiné Jr., T. Charles (Canadian Journal of Zoology, 1978)
Reproductive tracts were collected from 532 female caribou (Rangifer tarandus groenlandicus) in northern Canada over a [Formula: see text]-year period. Ovaries were weighed and scrutinized by gross and histological techniques. Ovaries of nulliparous and nongravid, parous cows responded to follicular fluctuations by increasing in weight in summer and declining in winter. Weights of ovaries from calves, yearlings, and 2 year olds overlapped extensively. Formation of corpora lutea of pregnancy more than doubled ovary weight. During gestation ovary weight declined and then partially recovered; it increased with age in pregnant cows. The number and size of follicles [Formula: see text] diameter increased with age until puberty, reaching greatest development just before the autumn rut. After puberty the seasonal incidence of such follicles remained stable except during gestation, when it declined. Corpora lutea of pregnancy regressed to form apparently permanent scars composed of vascular and connective tissue remnants. Secondary corpora lutea developed in 35% of the cows at or before conception and upon regression produced scars which were not permanent. Regressing corpora lutea of estrus also disappeared into the ovarian stroma, apparently within 1 year. In individual cows one ovary, selected at random, dominated in the production of ova and corpora lutea.